Row division method to generate QC-LDPC codes - Yahya, A.; Sidek, O.; Salleh, M. F. M.; Farid, Ghani, Prof. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/